Birds Consumed by the Invasive Burmese Python (Python molurus bivittatus) in Everglades National Park, Florida, USA - Dove, Carla J.; Snow, Ray W.; Rochford, Michael R.; Mazzotti, Frank J. (The Wilson journal of ornithology, 2011)
We identified 25 species of birds representing nine avian Orders from remains in digestive tracts of 85 Burmese pythons (Python molurus bivittatus) collected in Everglades National Park, Florida, USA, from 2003 to 2008. Four species of birds identified in this study are of special concern in Florida and a fifth, the Wood Stork (Mycteria americana), is listed as federally endangered. This represents the first detailed analysis of the avian component of the diet of the introduced Burmese python, now established in Everglades National Park, Florida and highlights the potential for considerable negative impact of this invasive species on native bird populations.